Stress management application for young adult / Nor Adilah Kalam - Kalam, Nor Adilah (2016)
Detecting stress is very important, especially for young adults who are easily distracted with their surroundings. Some young adults do not know how to deal with stress and they do not even know what are the causes of their stress. They might easily take an easy method to cope with stress such as sleeping, eating and exercising. However, it is dangerous, when they take negative solutions such as committing suicide, hurting themselves and smoking. Furthermore, most young adults do not trust psychologist or they have difficulties in finding psychologists. Therefore, this project’s aim is to help young adults to explore and resolve their own problems. This project is a chatbot like application which implements Motivational Interviewing (MI) technique. This MI is a method in psychology that used can help young adult with stress. This chatbot implemented the knowledge of an expert which is a psychologist from Hospital Universiti Sains Malaysia (HUSM). The chatbot can help the young adults to manage their stress by following the techniques from MI and this might help the young adult from taking negative solutions. The system works by asking questions to the users, so that the users themselves can explore or discover their problems and its solutions. At the end of the chat session, a summary of the conversation is displayed. The project is implemented in Malay language and it is a stand-alone system. For the future, the chatbot application can be improved by featuring more questions, implementing the ability to store the data from previous sessions and also making the application accessible through the web. The feature of tracking emotional change of the users before and after using can also be added as one of future features.